Hope And Motivation Reflected On The Novels The Land Of Five Towers (2011) By Ahmad Fuadi, The Rainbow Troops (2009) And Edensor (2011) By Andrea Hirata: An Individual Psychological Approach - Widiyati, Wiwik, Dewi Candraningrum, Ph.D, Dr. Abdillah Nugroho, M.Hum (2015)
The objectives of the research are: 1) to describe the concept of hope reflected in the novels The Land of Fives Towers by Ahmad Fuadi, The Rainbow Troops and Edensor by Andrea Hirata; 2) to describe the concept of motivation is reflected in the novels The Land of Fives Towers by Ahmad Fuadi, The Rainbow Troops and Edensor by Andrea Hirata. The type of the research used by the researcher was qualitative research. In this study, the researcher wants to describe systematically, factually, and accurately an interest of one of the intrinsic factor of novel, they were hope and motivation reflected in the novels. The researcher used the descriptive method to analyze hope and motivation. The data were the novels "The Land of Five Towers" written by Ahmad Fuadi (A. Fuadi). "The Rainbow Troops" written by Andrea Hirata in 2009, and the novel "Edensor" written by by Andrea Hirata in 2011, consists of 238 pages, devided into 40 chapters, published by PT. Bentang Pustaka. The results of the research showed that the concept of hope in The Land of Five Towers was in the emphasis of Man Jadda Wajada spirit. The concept of hope in Andrea Hirata's The Rainbow Troops was reflected in the hope of getting better life. It was reflected in the form of conative aspect, they were expectation and desire. The concept of hope in Andrea Hirata's Edensor was gaining a dream or people who do not have any dream. The concept of motivation in The Land of Five Towers was a high work ethic to set a goal to reach a certain hope in certain time. Qur'an reminds not to be like those who forgot Allah did not complete the obligation. Therefore, whoever always pays attention to their success in the hereafter would be motivated to write as part of worship and it could add a lot of good reward. The concept of motivation in The Rainbow Troops was naturally gravitate to mutual interests, and they enjoy talking as they share likes, dislikes, goals and dreams. That kind of a motivation exists with friends that they could trust each other to keep their secrets and confidences. The concept of motivation in Edensor was Andrea Hirata dream when he was child and his experiences as backpacker in two continents.